2019
DOI: 10.1039/c9ra06797c
|View full text |Cite
|
Sign up to set email alerts
|

Bulky cations greatly increase the turnover of a native hammerhead ribozyme

Abstract: Large tetraalkylammonium ions increase the turnover rate of the ribozyme derived from an intronic ribozyme in the human genome. The rate can be enhanced by more than a hundred-fold at the optimal concentrations of Mg2+ and TPeA ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…[18] We previously reported that TPeA and TBA ions can increase the turnover rate of the native ribozyme HH10 derived from an intronic ribozyme in the human genome. [19] However, the mechanism for regulating the turnover rate is not understood. Here, several types of watersoluble organic cations are evaluated with truncated and extended hammerhead ribozymes derived from Schistosoma mansoni, which exhibit different kinetic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[18] We previously reported that TPeA and TBA ions can increase the turnover rate of the native ribozyme HH10 derived from an intronic ribozyme in the human genome. [19] However, the mechanism for regulating the turnover rate is not understood. Here, several types of watersoluble organic cations are evaluated with truncated and extended hammerhead ribozymes derived from Schistosoma mansoni, which exhibit different kinetic behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…At physiological pH level, the activity of HHRz depends on metal ions, especially Mg 2+ [23], which supports cleavage in vitro for a minimal, but sub-optimal, HHRz sequence at 10 mM [24]. Other ions can also activate the self-cleavage of HHRz [25]: cations like ammonium (NH 4 + ) can support the activity of HHRz [26] and large tetraalkylammonium ions significantly increase the rate of HHRz in addition to Mg 2+ [27]. The cleavage rate of HHRz was tested with transition metals and depending on the conditions and ribozymes tested, cleavage with Mn 2+ showed three times [28] and up to seventy-six times [29] better cleavage than Mg 2+ .…”
Section: Introductionmentioning
confidence: 99%